GAMBARAN PENYEMBUHAN LUKA POST SECTIO CAESAREA DI RUANG BERSALIN RSI SAKINAH MOJOKERTO - Purwati, Heni (JURNAL KEPERAWATAN BINA SEHAT, 2012)
Early mobility following a Sectio Caesarea is a movement, position or activities done a fewhours after cesarean delivery. In post Sectio Caesarea there were changes in their bodies caused by delivery that affect early mobility, such as post labor pains because the mother is unable or doesnt want to have early Sectio Caesarea mobility. Medical personnel should instruct the mother on the importance of early mobility. The aim of this research is to describe the current knowledge concerning early mobility following a Sectio caesarea. The method used for this study is descriptive research. The population of this study are all post sectio caesarea mother’s from 1-20 April 2012 in wahidin sudirohuso mojokerto hospital by using the consecutive sampling technique on 20 respondents. The data was taken from a questionnaire and the research was done on 14-20 April 2012. From the data, it is known that 14 respondents (70%) have missing knowledge about early mobility in post sectio caesarea. These respondents did not receive information directly from the hospital personnel or indirectly through TV, books and other mass media sources. They did not know that they should be more active and motivate themselves to be more mobile post section caesarea.Keyword : Knowladge, early mobility, post sectio caesarea